1975
DOI: 10.1111/j.1095-8649.1975.tb04620.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the swimming musculature of the rainbow trout I. Fibre types

Abstract: A histochemical study has been made 011 the myotomal musculature of the rainbow trout SaEmo gaivdnevi Richardson. Four main types of fibre can be distinguished on the basis of differences in fibre size, lipid content and succinic dehydrogenase and myofibrillar adenosine triphosphatase activity (ATPase activity). Early histological studies have concluded that in addition to a superficial strip of muscle small diameter ' red ' fibres occur throughout the trout myotome. These small diameter fibres occurring in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
3

Year Published

1980
1980
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(56 citation statements)
references
References 25 publications
2
51
3
Order By: Relevance
“…Namely, the histochemical characteristics of pink muscle fibers in both ordinary and intermediate muscles were very similar. The same findings were reported in the rainbow trout (Johnston et al, 1975), and we reported that the temporal change of K-value in the dorsal ordinary muscle of carp was accelerated by the interposition of pink muscle fibers (Yada et al, 2000). It was therefore thought that the interposition of pink muscle fibers into the ordinary muscle might cause a temporal change in K-value (one item of the freshness index), which might be explain the difference in the increasing K-value rate among fish species.…”
Section: Discussionsupporting
confidence: 77%
“…Namely, the histochemical characteristics of pink muscle fibers in both ordinary and intermediate muscles were very similar. The same findings were reported in the rainbow trout (Johnston et al, 1975), and we reported that the temporal change of K-value in the dorsal ordinary muscle of carp was accelerated by the interposition of pink muscle fibers (Yada et al, 2000). It was therefore thought that the interposition of pink muscle fibers into the ordinary muscle might cause a temporal change in K-value (one item of the freshness index), which might be explain the difference in the increasing K-value rate among fish species.…”
Section: Discussionsupporting
confidence: 77%
“…Forstner et al (1983) observed several changes in muscle development in coregonid larvae reared at 10°C. The authors observed a thin layer of 'small diameter red fibres' (described by Johnston et al 1975) from Day 4 on, which made up to 9% of the total muscle mass on Day 20. Increase in this muscle mass was realised by increasing cell numbers and not by increasing the diameter of the cells, so hyperplasia can be assumed to be present in this type of muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The myotomal muscle of teleosts contains two main fibre types, grouped in two layers: (1) subdermal red muscle, with oxidative metabolism and slow contraction, and (2) deep white muscle, with glycolytic metabolism and fast contraction (Johnston et al 1975(Johnston et al , 1977Bone 1978). Between those layers, an intermediate zone is found, with fibres characterised by being essentially fast contracting, with both intermediate resistances to fatigue and shortening speed (Johnston et al 1977).…”
Section: Introductionmentioning
confidence: 99%